PENGARUH KARAKTERISTIK INDIVIDU, KARAKTERISTIK PEKERJAAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BANK SUMSEL BABEL CABANG SYARIAH PALEMBANG - Muhammad Rizka Sya'ban; Lemiyana, Lemiyana; Juniawati , Mutmainah (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
The purpose of this research is to determine the influence of individual characteristics, job characteristics and organizational culture on the performance of employees of Bank Sumsel Babel Syariah Branch, Palembang. This type of research is quantitative. The data used is primary data. The population in this study were employees of Bank Sumsel Babel, Palembang Syariah Branch, totaling 35 respondents. Sampling in this research was carried out using saturated sampling techniques. Data analysis in this study used multiple linear regression and data processing was assisted by the IBM SPSS Statistics 21 application. The results of the study showed that individual characteristics and organizational culture had a significant effect on the performance of employees of the South Sumatra Babel Syariah Palembang Branch. Meanwhile, job characteristics do not have a significant effect on the performance of South Sumatra Babel Palembang Syariah Branch employees. Simultaneously individual characteristics, job characteristics and organizational culture have a significant effect on the performance of employees of the South Sumatra Babel Palembang Sharia Branch.